Konsep keluarga sakinah dalam keluarga karir menurut hukum Islam (studi kasus Desa Asembagus, Kecamatan Kraksaan) - Rohmatullah, Rizki; Syafi’i, Imam (AL-MUQARANAH, 2024)
Creating a sakinah mawaddah warahmah family is a benefit for every married couple in the midst of modernization which is currently taking place and has an impact on the socio-cultural environment around the family. Along with the times, the development of society's mindset and the increasingly intense struggle for gender equality in society, there is still perceived inequality towards women, then gradually women are starting to struggle to take their position in the public arena. The research method used is qualitative/field research (field research) where this research is descriptive. The data collection method was carried out through observation and interviews. The data sources used come from primary data and secondary data. The data analysis used is qualitative data analysis with an inductive thinking approach. Based on the research results, it was concluded that the concept of Sakinah in the career family according to Islamic law in Asembagus Village was formed on the basis of strong religion and an attitude of mutual openness and mutual respect between family members, working together to meet the needs of the family both spiritually and spiritually. honesty and tolerance taught to children and other family members, as well as always being grateful for the blessings and sustenance given by Allah SWT.